A Study of Large Sheave Counter-Roller Spinning Force. Issue 1 (1st June 2022) - Zhu, Chengcheng; Li, Fan; Meng, Dean; Dong, Yuanzhe
Abstract: In this paper, a counter-roller spinning method is presented, which is designed to produce relatively thin-walled large sheaves. The large sheave counter-roller spinning force is poorly studied. And the forming forces have a significant influence on industrial applications. Herein, theoretical analysis and numerical simulation methods were utilized to explore the large sheave counter-roller spinning process and spinning force. Anisotropy of the material was considered by the Hill-48 anisotropic yield criterion. Numerical simulation has been demonstrated to correspond to experimental values. The spinning forces in the simulation and experiment matched well and steadily increased throughout the process. The roller and mandrel have similar spinning forces, and the radial spinning force is much larger than other forces. Finally, a theoretical model to compute the spinning force was constructed.